PERK signaling through C/EBPδ contributes to ER stress-induced expression of immunomodulatory and tumor promoting chemokines by cancer cells - Namratha Sheshadri (Nature Publishing Group, 2021)
Abstract Cancer cells experience endoplasmic reticulum (ER) stress due to activated oncogenes and conditions of nutrient deprivation and hypoxia. The ensuing unfolded protein response (UPR) is executed by ATF6, IRE1 and PERK pathways. Adaptation to mild ER stress promotes tumor cell survival and aggressiveness. Unmitigated ER stress, however, will result in cell death and is a potential avenue for cancer therapies. Because of this yin-yang nature of ER stress, it is imperative that we fully understand the mechanisms and dynamics of the UPR and its contribution to the complexity of tumor biology. The PERK pathway inhibits global protein synthesis while allowing translation of specific mRNAs, such as the ATF4 transcription factor. Using thapsigargin and tunicamycin to induce acute ER stress, we identified the transcription factor C/EBPδ (CEBPD) as a mediator of PERK signaling to secretion of tumor promoting chemokines. In melanoma and breast cancer cell lines, PERK mediated early induction of C/EBPδ through ATF4-independent pathways that involved at least in part Janus kinases and the STAT3 transcription factor. Transcriptional profiling revealed that C/EBPδ contributed to 20% of thapsigargin response genes including chaperones, components of ER-associated degradation, and apoptosis inhibitors. In addition, C/EBPδ supported the expression of the chemokines CXCL8 (IL-8) and CCL20, which are known for their tumor promoting and immunosuppressive properties. With a paradigm of short-term exposure to thapsigargin, which was sufficient to trigger prolonged activation of the UPR in cancer cells, we found that conditioned media from such cells induced cytokine expression in myeloid cells. In addition, activation of the CXCL8 receptor CXCR1 during thapsigargin exposure supported subsequent sphere formation by cancer cells. Taken together, these investigations elucidated a novel mechanism of ER stress-induced transmissible signals in tumor cells that may be particularly relevant in the context of pharmacological interventions.